(untitled) - Rosemary Scott (Oxford, 1994)
This book offers elementary students of English a wide variety of authentic reading material, including poetry. The texts are grouped together by theme. The exercises are task-based and developed skills in global and intensive reading, pre-reading and predicting, and vocabulary development. The book contains an introduction to the teacher and a Key
Keywords: english language - study and teaching,english language - textbooks for foreign speakers,readers,reading